Alternative soilless media for growing Petunia × hybrida and Impatiens wallerana: Physical behavior, effect of fertilization and nitrate losses - Chavez, Walter (2008)
The use of alternative soilless media for the production of potted plants requires knowledge of their physical and chemical characteristics to result in the best conditions for plant growth. We investigated the use of alternative soilless media based on river waste and Sphagnun sp. and Carex sp. from Argentinean peatlands on Petunia × hybrida and Impatiens wallerana production at two fertilization levels (200 and 400 mg l-1 N). River waste or 'temperate peat' is the name given to a material, resulting from the accumulation of aquatic plant residues under an anaerobic subtropical environment, which is dredged from river banks. Our results showed that alternative substrates based on river waste can be used to grow high quality plants. This result was not fully explained on the basis of established methods to evaluate substrate quality. Highly concentrated fertigation solution decreased the substrate quality parameters and plant growth. Nitrate leaching from the alternative substrates containing river waste was lower than the standard peat-based materials, which makes river waste desirable from a sustainable pot production system perspective. River waste and Carex peat are suitable alternatives to Sphagnum peat from the Northern Hemisphere. © 2008.